2004
DOI: 10.1088/0953-8984/16/36/008
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigations of the antiferromagnetic   phase of solid oxygen at low pressure (up to 1.25 GPa)

Abstract: Elementary magnon, libron and vibron excitations as well as combined two-libron excitations of solid α oxygen have been investigated by means of Raman scattering at several isobars in the pressure range up to 1.25 GPa. We deduced the band frequency, bandwidth and relative band intensity of all modes as a function of temperature and pressure. On the basis of these results we can exclude the possibility of all second-order phase transitions in the low temperature, low pressure range of oxygen stated in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Whereas the magnon mode vanishes with increasing pressure, the two-libron excitations are seen throughout the ␣ phase and become more intense at higher pressures. This trend-already observed at low pressure 16 -continues even in the ␦ phase, where also the two-libron excitations exist. The intensity of the two-libron excitations relative to the intensity of the one-libron excitations is shown in the inset in Fig.…”
Section: Magnetism In the ␣ And ␦ Phasessupporting
confidence: 54%
See 4 more Smart Citations
“…Whereas the magnon mode vanishes with increasing pressure, the two-libron excitations are seen throughout the ␣ phase and become more intense at higher pressures. This trend-already observed at low pressure 16 -continues even in the ␦ phase, where also the two-libron excitations exist. The intensity of the two-libron excitations relative to the intensity of the one-libron excitations is shown in the inset in Fig.…”
Section: Magnetism In the ␣ And ␦ Phasessupporting
confidence: 54%
“…32 These we explained as originating with magnetic coupling of two molecules in the primitive cell performing librations. In our recent low-pressure Raman study 16 on ␣ oxygen we found that due to an enhancement of the spin coupling mechanism, the intensities of two-libron excitations increase by a factor of about 5 as one applies pressure from 0 to 1.25 GPa. Therefore, the pressure dependence of frequencies and intensities of these two-libron excitations have to be investigated in the pressure range up to 8 GPa to obtain Raman spectroscopic information about magnetism of the high-pressure ␣ phase and the ␦ phase at low temperatures.…”
Section: Magnetism In the ␣ And ␦ Phasesmentioning
confidence: 82%
See 3 more Smart Citations